2019
DOI: 10.1101/724427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic 3D chromosomal landscapes in acute leukemia

Abstract: ABSTRACTThree-dimensional (3D) chromatin architectural changes can alter the integrity of topologically associated domains (TADs) and rewire specific enhancer-promoter interactions impacting gene expression. Recently, such alterations have been implicated in human disease, highlighting the need for a deeper understanding of their role. Here, we investigate the reorganization of chromatin architecture in T cell acute lymphoblastic leukemia (T-ALL) using primary human leukemia sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…1A, lower tracks), which has also been suggested to mark active enhancer regulatory elements (20,21). Finally, analyses of publicly available H3K27ac Hi-ChIP data in CUTLL1 T-ALL cells (19) revealed that, among the different interacting regions with the PTEN promoter, the interaction with the PE enhancer is the only one detected at FDR <1E-15 ( Fig. 1A, top).…”
Section: Identification Of Pe a Pten Enhancer In T-allmentioning
confidence: 75%
See 1 more Smart Citation
“…1A, lower tracks), which has also been suggested to mark active enhancer regulatory elements (20,21). Finally, analyses of publicly available H3K27ac Hi-ChIP data in CUTLL1 T-ALL cells (19) revealed that, among the different interacting regions with the PTEN promoter, the interaction with the PE enhancer is the only one detected at FDR <1E-15 ( Fig. 1A, top).…”
Section: Identification Of Pe a Pten Enhancer In T-allmentioning
confidence: 75%
“…1A, CTCF track), suggesting that cohesin-mediated loops might be responsible for this interaction (15)(16)(17)(18). In addition, GRO-seq analyses of T-ALL cells (19) uncovered bi-directional transcription from this region (Fig. 1A, lower tracks), which has also been suggested to mark active enhancer regulatory elements (20,21).…”
Section: Identification Of Pe a Pten Enhancer In T-allmentioning
confidence: 82%
“…In fact, only a small number of patient Hi-C datasets have been generated. For instance, Kloetgen et al have produced and studied Hi-C data for six primary T-cell acute lymphoblastic leukemia (T-ALL) patients [32], and Díaz et al have done so for one large B-cell lymphoma patient [33]. To conduct an independent validation of some of our results, we compared a list of 37 TADs that have been reported to undergo structural changes in the B-cells of lymphoma patients [33] to our normal consensus TADs; we observed that 78% (29/37) of these 37 TADs overlapped by at least 90% with our consensus TADs, but only 8% (3/37) overlapped with constitutive TADs, while the expectation based on their sizes is 27% (10/37).…”
Section: Discussionmentioning
confidence: 99%
“…This promising study interrogating the disruption of long-distance interactions between enhancers and promoters might lead the way to new cancer treatment options targeting the 3D genome organization. Furthermore, it has been shown that a fusion of two TADs accompanied by an almost complete loss of CTCF binding at the boundary between these two TADs leads to an interaction between the MYC promoter and a distal super-enhancer in primary T-ALL samples as well as T-ALL cell lines (72). The increased looping events can be inhibited by using small molecule inhibitors against oncogenic signaling molecules or epigenetic modifiers (72).…”
Section: Novel Approaches For Hematological Malignancies and Future Pmentioning
confidence: 99%
“…Furthermore, it has been shown that a fusion of two TADs accompanied by an almost complete loss of CTCF binding at the boundary between these two TADs leads to an interaction between the MYC promoter and a distal super-enhancer in primary T-ALL samples as well as T-ALL cell lines (72). The increased looping events can be inhibited by using small molecule inhibitors against oncogenic signaling molecules or epigenetic modifiers (72). Another study reveals that a mutation within the EZH2 gene encoding a histone lysine methyltransferase and present among others in non-Hodgkin lymphomas leads to increased H3K27me3 as well as changes in the TAD structure resulting in intra-TAD gene silencing, which can be restored by pharmacological inhibition of the mutant EZH2 (73).…”
Section: Novel Approaches For Hematological Malignancies and Future Pmentioning
confidence: 99%